Inverse Scattering Problem on the Axis for the Schrödinger Operator with Triangular 2 x 2 Matrix Potential. I. Main Theorem - Zubkova, E. I.; Rofe-Beketov, F. S. (Журнал математичної фізики, аналізу, геометрії, 2007)
The necessary and sufficient conditions for solvability of ISP under consideration are obtained. Mathematics Subject Classification: 47A40, 81U40.